Prosthetic rehabilitation of an adolescent with ectodermal dysplasia utilizing multidisciplinary approach: A case report (Indian Journal of Case Reports, 2020)
Ectodermal dysplasia (ED) is a hereditary disorder characterized by abnormal development of two or more embryonic ectodermal structures such as skin, nails, teeth, hair, eyes, and sweat glands. The main oral manifestations of ED include oligodontia, malformed teeth and, deficient alveolar ridges. Inheritance of ED is X-linked and expressed typically in males. This case report explains a multidisciplinary treatment of a 16-year-old adolescent suffering from ED with underdeveloped premaxilla, underdeveloped alveolar ridges, retained deciduous teeth, and thick fibrous frenal attachment. Prosthetics rehabilitation was done using removable cast partial dentures with lip support. It also enumerates the important role of a multidisciplinary approach in dental treatment, helping the patient’s healthy transition from childhood to adulthood. Dental professionals should be able to identify the oral features of ED and provide proper oral care (as early as 3–4 years) to restore the oral functional demands and esthetics.